Pricing the priceless: A history of environmental economics - Banzhaf, H. Spencer (New York Cambridge University Press, 2024)
While large literatures have separately examined the history of the environmental movement, government planning, and modern economics, Pricing the Priceless triangulates on all three. Offering the first book-length study of the history of modern environmental economics, it uncovers the unlikely role economists played in developing tools and instruments in support of environmental preservation.